Cleft lip scar correction methods (Journal of Face Aesthetics, 2019)
Introduction. A cleft lip is a congenital malformation that may appear as an independent defect or as one of many syndrome features. Primary cleft lip surgical treatment is the only method of treatment to achieve tissue continuity, however it is associated with the inevitable postoperative scar and the emergence of so‑called secondary disorders, which has got a negative impact on psychosocial patient’s development.Aim. Presentation of possibilities of cleft upper lip scar correction paying attention to facial aesthetics.Material and Methods. The literature search was conducted in the English language via the PubMed database and Main Medical Library. The articles regarding cleft upper lip scar correction and care methods were selected.Results. All the methods of postoperative scar management presented in the results proved to be an effective way of cleft scar correction. These methods concern: surgical procedures, mechanical intervention, laser treatment, and medical therapy with using medicines and are dependent on the type of irregularity. These methods allowed to improvement of the aesthetics of the upper lip area and enabled control and prevention of cleft scar hypertrophy.Conclusions. There is no one procedure regarding the care and correction of cleft scars. Postoperative scar management should be adjusted individually to each patient, analyzing the medical case, to get the best possible aesthetic and functional effect.
Keywords: scar hypertrophy; scar contracture; surgical correction; laser treatment